Digital marketing in hospitality - Case study Hotel Manstir - Dafinka Mucunska; Dejan Nakovski (UTMS Journal of Economics, 2022)
In recent decades, hospitality has become one of the largest, fastest growing and most dynamic industrial sectors. It is an industry that includes many complementary businesses from many different fields. The impact of new technologies has played a fundamental role in the growth of the entire catering business. Digital marketing has changed the way people communicate, receive information and, to a large extent, the way they make purchasing decisions, which has a particular impact on the hotel business. In order to understand the essence of the use of digital marketing in the hotel business, the central idea that is discussed in this paper is: "Digital marketing, a special opportunity for growth and development of the hotel business." This thesis aims to highlight the basic attributes of digital marketing and its channels, focusing in particular on the hotel sector. Digital marketing today is the primary marketing path in the hospitality industry and is the key to gaining and maintaining a competitive advantage. In the case of the hotel sector, where marketing is one of the core business activities, digital marketing has quickly gained great importance, both for better informing consumers and for developing more sophisticated strategies to increase market visibility
Keywords: L83; Z32; I15; O18; 330; tourism; inventions; technology; internet